Community Service : Promotion Of Healthy Snack Nutritions At Jaranan Elementary School - Sarni Anggoro (Humanism: Journal of Community Empowerment (HJCE), 2020)
School-age children are the nation's next generation who have the potential to advance development in the future. A quarter of the time a day is spent by children at school, so the nutrition of eating or snacks the child needs to be a serious concern that needs to be monitored and fulfilled properly. Lack of knowledge of students causes them to snack in accordance with their preferences without thinking about food snacks that are exposed to physical contamination, biological chemistry and other dangerous substances. Community service is about the promotion of nutrition about healthy snacks. The purpose of this activity is to get students used to eating healthy foods. Health education methods and demonstrations were chosen to provide information about healthy snacks. The pretest posttest method is used to evaluate students' knowledge before and after health education is given about nutrition of healthy snacks. Respondents in this community service are Jaranan Elementary School students. The results showed an increase in students' knowledge about healthy snacks and observations made by the implementers with the help of teachers showed data that students had chosen and consumed healthy snacks as snacks at school.